CCCDTD5: Individual and community‐based psychosocial and other non‐pharmacological interventions to support persons living with dementia and their caregivers. Issue 1 (11th November 2020) - Vedel, Isabelle; Sheets, Debra; McAiney, Carrie; Clare, Linda; Brodaty, Henry; Mann, James; Anderson, Nicole; Liu‐Ambrose, Teresa; Rojas‐Rozo, Laura; Loftus, Lynn; Gauthier, Serge; Sivananthan, Saskia
Abstract: Introduction: Current pharmacological therapies for dementia have limited efficacy. Thus it is important to provide recommendations on individual and community‐based psychosocial and non‐pharmacological interventions for persons living with dementia (PLWDs) and their caregivers. Methods: Phase 1: A systematic review for developing recommendations on psychosocial and non‐pharmacological interventions at the individual and community level for PLWDs and their caregivers. Phase 2: Rating of recommendations using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) guidelines. Phase 3: Delphi process (>50 dementia experts) for approving recommendations by the 5 th Canadian Consensus Conference on the Diagnosis and Treatment of Dementia (CCCDTD5). Results: The CCCDTD5 approved the following recommendations: Exercise (1B) and group cognitive stimulation for PLWDs (2B), psychosocial and psychoeducational interventions for caregivers (2C), development of dementia friendly organization and communities (2C), and case management for PLWDs (2B). Discussion: The CCCDTD5 provides for the first time, evidence‐based recommendations on psychosocial and non‐pharmacological interventions for PLWDs and their caregivers that can inform evidence‐based policies for PLWDs in Canada.